Exploring the potential therapeutic effect of Eucommia ulmoides–Dipsaci Radix herbal pair on osteoporosis based on network pharmacology and molecular docking technology. Issue 4 (14th January 2022) - Feng, Shuai; Wang, Ting; Fan, Liming; An, Xinxin; Ding, Xinli; Wang, Minjuan; Zhai, Xifeng; Cao, Yanjun; He, Jiao; Li, Yang
Abstract : This study elaborated the multi-component, multi-target, and multi-pathway interaction mechanism of Eucommia ulmoides-Dipsaci Radix herbal pair in the treatment of osteoporosis. Abstract : Eucommia ulmoides – Dipsaci Radix (EU–DR) is a commonly used herbal pair for the treatment of osteoporosis (OP) in China. The purpose of this study was to investigate the potential mechanism of EU–DR on OP through network pharmacology and molecular docking approaches. Combining data from multiple open-source databases and literature mining, the active compounds and potential targets of EU–DR were screened out. The OP related targets were identified from the interactive web tool GEO2R. The shared targets were obtained by intersecting the targets of EU–DR and OP. The protein–protein interaction (PPI) network was constructed via the STRING database and Cytoscape 3.7.2 software. GO and KEGG enrichment analysis were conducted using R 3.6.3 software with adjusted p -value < 0.05. Sybyl-x 2.1.1 and Autodock Vina 1.1.2 software were used to cross validate the affinity between active compounds and target proteins. Our results showed that a total of 50 active compounds were screened, corresponding to 895 EU–DR targets, 2202 OP targets and 144 shared targets. The flavonoids in EU–DR played an important role in anti-OP. The enrichment analysis of GO and KEGG suggested EU–DR exerted a therapeutic effect on OP mainly by regulating the osteoclast differentiation related signaling pathway. Meanwhile, molecular docking results showed that most active compounds in EU–DR had strong binding efficiency to the target proteins. In conclusion, this study elaborated the multi-component, multi-target, and multi-pathway interaction mechanism of the EU–DR herbal pair in the treatment of OP for the first time, which also provided a pharmacological basis for treating OP.